'To market, to market': uncovering Daigou touristscapes within Chinese outbound tourism. Issue 4 (2nd October 2021) - Zhang, Xiaoyu (Nancy); Tham, Aaron; Liu, Yulin; Spinks, Wendy; Wang, Liang
ABSTRACT: Daigou may be simply understood as purchasing on behalf of others. However, as an informal economy, Daigou trade between buyers and sellers is now a lucrative market and has emerged as a distinctive tourism segment. While Daigou occurs on the back of technological platforms that facilitate electronic commerce between customer to customer, academic literature on Daigou from a Chinese outbound tourism perspective remains scarce. Prompted by this dearth in knowledge, this research explores the emerging practices of Daigou tourists as a subset of Chinese outbound tourism through an online questionnaire survey conducted with 300 respondents from Beijing, Shanghai, and Guangzhou. Through descriptive statistics and Multiple Correspondence Analysis, the research revealed that Daigou tourism is a heterogenous market and are driven by product quality, profit margins and country of origin associations. This offers distinct theoretical and managerial contributions and elucidates a more nuanced understanding of the Daigou phenomenon as a fluid, under-regulated and micro-entrepreneurial practice in tourism.